The Influence of Family Income, Living Environment and Education on Poverty in Palopo City - Ahmad Refki Saputra; Hapid; Jusman; Adi Firmanzah (IECON: International Economics and Business Conference, 2024)
This study examines the influence of family income, living environment, and education on poverty levels in Palopo City. Utilizing secondary data from the Palopo City Central Statistics Agency, the research analyzes the relationship between these exogenous variables—family income, living environment, and education—and the endogenous variable of poverty. The study employs panel data, combining time series and cross-sectional data, and uses quantitative analysis through path analysis to evaluate the relationships. The findings reveal that all proposed hypotheses are supported. Hypothesis 1 confirms that family income has a significant positive effect on poverty in Palopo City, indicating that lower family income levels are strongly associated with higher poverty rates. Hypothesis 2 establishes that the living environment has a positive and significant effect on poverty, suggesting that poor living conditions contribute substantially to poverty levels. Hypothesis 3 demonstrates that education also has a positive and significant effect on poverty, implying that limited educational attainment exacerbates poverty issues. These results underscore the interconnectedness of income, environmental conditions, and education in shaping poverty dynamics. The findings highlight the need for integrated policy interventions aimed at improving family income, enhancing living conditions, and increasing educational access to effectively combat poverty in Palopo City. Future research could explore other potential determinants and their interaction with these factors.